2020
DOI: 10.1002/jeq2.20165
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of available phosphorus in soil: Combined use for crop production and water quality protection

Abstract: Optimizing phosphorus (P) application to agricultural soils is fundamental to crop production and water quality protection. We sought to relate soil P tests and P sorption characteristics to both crop yield response to P application and environmentally critical soil P status. Barley (Hordeum vulgare L.) was grown in pot experiments with 45 soils of different P status. Half the pots were fertilized at 20 kg P ha −1 , and half received no P. Soils were extracted with ammonium lactate, sodium bicarbonate (Olsen P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In pot experiments with barley ( Hordeum vulgare L.) growing in 45 noncalcareous soils from Norwegian farms, Kristoffersen et al. (2020) recently documented a DPS threshold of 35% at which there was no yield response to applications of P. According to this threshold, we expected to see a response to P application at Landvik‐NO and especially at Princen‐NL, but not at Düte‐DE and Falken‐SE. As for the MLSN guidelines, a response was expected at Princen‐NL, Jingshan‐CN, and Düte‐DE, but not at Falken‐SE and Landvik‐NO.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In pot experiments with barley ( Hordeum vulgare L.) growing in 45 noncalcareous soils from Norwegian farms, Kristoffersen et al. (2020) recently documented a DPS threshold of 35% at which there was no yield response to applications of P. According to this threshold, we expected to see a response to P application at Landvik‐NO and especially at Princen‐NL, but not at Düte‐DE and Falken‐SE. As for the MLSN guidelines, a response was expected at Princen‐NL, Jingshan‐CN, and Düte‐DE, but not at Falken‐SE and Landvik‐NO.…”
Section: Discussionmentioning
confidence: 88%
“…Values of Al ox varied from 0.08 to 0.24 g kg –1 , and Fe ox varied from 0.22 to 0.61 g kg –1 soil. For comparison, data from 45 cultivated Norwegian soils showed Al ox values in the range of 0.9 to 5.3 g kg –1 and Fe ox values in the range of 2.1 to 10.1 g kg –1 soil (Kristoffersen et al., 2020). The low PSC values are mainly caused by the sandy soil, which has particles with a low specific surface area and therefore relatively few binding sites for phosphate ions, resulting in a fast increase in DPS when surplus P was added.…”
Section: Discussionmentioning
confidence: 99%
“…After a dose of manure application, Liu et al (2012) found greater increases in DRP concentrations, as compared to before the application, in drainage from topsoils with higher degrees of P saturation than from those with lower P saturation. Also, Kristoffersen et al (2020) showed low P adsorption in high-P soils. Given many soils in our study catchment had high soil test P, any increase in P saturation might accelerate DRP concentrations in drainage.…”
Section: The Importance Of P Surplus and Soil Test P In Affecting Cat...mentioning
confidence: 92%
“…The regulation is implemented with the aim to reduce surplus manure P inputs on livestock farms, because large quantities of manure input increase the risk of P loss not only over a crop season or a year but also over a long term when the P input continuously builds up soil test P (a measurement of plant available form of P) (Bechmann, 2014b). Typically, concentration of soil test P increases with increasing P balances (Bechmann, 2014b), which consequently increases the concentrations of water-soluble P in the soil (Kristoffersen et al, 2020) and the concentrations of dissolved P in runoff (Liu et al, 2021). Although the regulation has been in place since 1989 (FOR-1989-03-01-151), soil P surplus remains a concern in livestock-intensive regions, especially when the historically large rates of manure applications are considered (Vagstad, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy may be influenced by limitations in the experimental setup specifically the duration of equilibration. Typically, sorption isotherms are developed through 24‐h incubation studies, overlooking the mid‐to‐long‐term dynamics of soil nutrient availability (Habibiandehkordi et al., 2014; Hussain et al., 2010; Kristoffersen et al., 2020). To assess the accuracy and reliability of sorption isotherms in fertilizer recommendations, it is beneficial to compare them with equilibration studies that employ longer incubation periods, such as the requirement factors that utilize a 6‐week timeframe.…”
Section: Introductionmentioning
confidence: 99%